2019
DOI: 10.14309/ajg.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Risk Scoring Systems in Ursodeoxycholic Acid–Treated Patients With Primary Biliary Cholangitis

Abstract: INTRODUCTION: Risk stratification based on biochemical variables is a useful tool for monitoring ursodeoxycholic acid (UDCA)-treated patients with primary biliary cholangitis (PBC). Several UDCA response criteria and scoring systems have been proposed for risk prediction in PBC, but these have not been validated in large external cohorts. METHODS: We performed a study on data of 1746 UDCA-treated patients with PBC from 25 centers in Europe, United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
3
24
1
2
Order By: Relevance
“…Several studies have validated the ability of Globe and UK-PBC risk scores to predict clinical outcomes in patients with PBC. [41][42][43] Absolute alkaline phosphatase and total bilirubin criteria at 1 year after the UDCA therapy have been used as a more robust predictor of hard endpoints such as liver transplantation or deaths of patients with PBC. 35 More recently, Zhang et al reported that earlier biochemical response to UDCA at 3 or 6 months was devised to identify patients at risk of poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have validated the ability of Globe and UK-PBC risk scores to predict clinical outcomes in patients with PBC. [41][42][43] Absolute alkaline phosphatase and total bilirubin criteria at 1 year after the UDCA therapy have been used as a more robust predictor of hard endpoints such as liver transplantation or deaths of patients with PBC. 35 More recently, Zhang et al reported that earlier biochemical response to UDCA at 3 or 6 months was devised to identify patients at risk of poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…50,69,70 Both the GLOBE and UK-PBC risk scoring systems were found to be predictive of cirrhosis-related complications based on a recent multicenter Turkish study. 71 Table 2 provides a review of current prognostication models.…”
mentioning
confidence: 99%
“…Moreover, there are no clear criteria that can reliably predict the response to UDCA. 15 Therefore, there were limitations to drawing conclusions from a single biochemical response criterion, which may lead to the misclassification of the clinical effect of UDCA in PBC patients. In this study, the Paris I criteria combined with the Barcelona criteria were defined as the study endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14] There are significant differences in the criteria for evaluating the UDCA response in PBC patients. 15 Given the potential risk of misidentification, the comprehensive evaluation of biochemical response can be superior to the use of a single criterion and could be helpful in risk stratification. In this study, we sought to retrospectively collect pretreatment clinical parameters, with the aim of identifying potential nonresponders to UDCA (defined by combined biochemical response criteria), using these clinical parameters to develop and validate a nomogram to facilitate decision-making.…”
Section: Introductionmentioning
confidence: 99%